(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2011)
The Social Security in the face of student of a university death. The Constitutional foundation. The juridical base of the Social Security Death. Section 77, of the Law 8213, and her interpretation in the face of present jurisprudence, of the STJ and of the TNU. About the doctrine in view of this proposition introduced. A constitutional interpretation and a constitutional below law interpretation for defence of the doctrine introduced. Conclusions.